COMPARATIVE ANALYSIS OF BONDING SYSTEMS FOR QUARTZ FIBER POSTS IN ROOT DENTINE - Firdausy, Muhammad Dian; Sugiharto, Reananda Mubarak; Hadianto, Eko; Hassan, Laila Azwa (Jurnal Medali, 2025)
Background: The success of bonding quartz fiber posts to root dentin hinges on various factors, including the bonding system. This experimental study aimed to investigate pull-out bond strength (PBS) of quartz fiber post toward root denting using different adhesive systems.Method: Thirty six human teeth (n=12) were embedded in acrylic resin blocks. Crowns were sectioned, leaving the root portion 20mm in length. Root canals were treated with standard endodontic protocols using the rotary instrument, obturated with gutta percha, and prepared for post cementation, leaving a 4mm apical seal. Root canals were prepared uniformly. After simple randomization, samples were divided into three groups according to the adhesive systems (Allcem core dual resin, NOVA resin self-adhesive, and GC FUJI Luting & Lining). Cementation procedures followed to manufacturer instructions. Post cementation was tested for PBS using a Universal Testing Machine (TN20 MD) until the posts were detached. Data were analyzed using the Kruskal-Wallis and Mann-Whitney U post hoc test (α=0.05)Result: The Kruskal-Wallis test indicated significant differences among the groups (P < 0.001), with GC FUJI Luting & Lining showing the significantly lowest PBS.Conclusion: Different cementation materials exhibit varying bond strengths. GC FUJI Luting & Lining provided inferior bond strength, making it the least recommended choice for bonding quartz fiber posts to root dentin.